EFFICACY OF POMEGRANATE PEEL EXTRACT, MANGOSTEEN PEEL EXTRACT, AND COMBINATION OF BOTH EXTRACT ON INCISION WOUND HEALING IN MICE - HASAN, HASMAWATI; OKTAWATY, SRI; KADANG, PRISCILIA MAUDY (International Journal of Applied Pharmaceutics, 2019)
Objective: The purpose of this research is to learn about the effectiveness difference between pomegranate peel extract, mangosteen peel extract, and combination of both extracts on incision wound healing of mice. Methods: This research is experimental research with post-test only control group design. The subjects used in this research were 24 male mice divided into group I pomegranate peel extract, group II mangosteen peel extract, group III combination of both peels, and group IV positive control (povidone-iodine). Every group of mice were then given the treatment, and the length of the wounds was measured and recorded daily until the seventh day after the incision was made, followed by data processing. Results: On the 7th day, the average wound length in group I was 0.45±0.06 cm, in group II was 0.16±0.25 cm, in group III was 0.0±0.0 cm, and in group, IV was 0.48±0.16 cm. By analyzing the data using Friedman and Wilcoxon test, it shows that there are significant differences between every group. Conclusion: The extract of pomegranate peel, mangosteen peel, and both combined are effective on incision wound healing of mice. The combination of pomegranate and mangosteen peel extract shows the best healing effect, followed by mangosteen peel extract, and pomegranate peel extract only.